Microwaves in nanoparticle synthesis - Horikoshi, Satoshi; Serpone, Nick, 1939- (Wiley-VCH ; John Wiley [distributor], 2013)
For the first time, this comprehensive handbook presents the emerging field of microwave technology for the synthesis of nanoparticles. Divided into three parts--fundamentals, methods, and applications--it covers topics including microwave theory, scale-up, microwave plasma synthesis, characterization, and more. This offers both an important volume for academic researchers, and a resource for those in industry exploring the applications of nanoparticles in semiconductors, electronics, catalysis, sensors, and more.